Antibacterial and anti-biofilm activities of probiotic Lactobacillus plantarum against Listeria monocytogenes isolated from milk, chicken and pregnant women - Abou Elez, Rasha M. M.; Elsohaby, Ibrahim; Al-Mohammadi, Abdul-Raouf; Seliem, Marwa; Tahoun, Asmaa B. M. B.; Abousaty, Amira I.; Algendy, Reem M.; Mohamed, Eman A. A.; El-Gazzar, Nashwa (Frontiers in Microbiology, 2023)
The present study aimed to identify the presence of Listeria spp. in various samples, including pasteurized milk, chicken fillets, and stool samples from pregnant women in Sharkia Governorate, Egypt. Additionally, the study identified the serotypes, virulence-associated genes, antimicrobial resistance patterns, and biofilm formation in L. monocytogenes isolates. Moreover, the antibacterial and anti-biofilm activity of Lactobacillus plantarum (L. plantarum) against L. monocytogenes isolates was investigated. A cross-sectional study was conducted from August 2021 to January 2022 to collect 300 samples of pasteurized milk, chicken fillets, and stool from pregnant women admitted to outpatient clinics of hospitals. The results showed that 32.7% of the samples were positive for Listeria spp., including L. innocua (48.9%), and L. monocytogenes (26.5%). Among all L. monocytogenes isolates, hlyA, actA, inlC, and inlJ virulence-associated genes were detected. However, the virulence genes plcB, iap, and inlA were found in 10 (38.5%), 8 (30.8%), and 25 (96.2%) isolates, respectively. The L. monocytogenes isolates classified into four serotypes (1/2a, 1/2b, 1/2c, and 4b), with 1/2a and 4b each identified in 30.8% of the isolates, while 1/2b and 1/2c were identified in 19.2% of the isolates. Multidrug resistance (MDR) was observed in 20 (76.9%) L. monocytogenes isolates. At 4°C, 25°C, and 37°C, 53.8%, 69.2%, and 80.8% of the isolates, respectively, were biofilm producers. Furthermore, 23.1% were strong biofilm producers at both 4°C and 25°C, while 34.6% were strong biofilm formers at 37°C. Treating L. monocytogenes isolates with L. plantarum reduced the number of biofilm-producing isolates to 15.4%, 42.3%, and 53.8% at 4°C, 25°C, and 37°C, respectively. L. plantarum's antibacterial activity was tested against six virulent, MDR, and biofilm-forming L. monocytogenes isolates, and the minimum inhibitory concentration required to inhibit visible growth of L. monocytogenes was 10 μg/mL. Transmission electron microscopy (TEM) revealed that L. plantarum induced morphological and intracellular structural changes in L. monocytogenes. In conclusion, this study identified virulent MDR L. monocytogenes isolates with strong biofilm-forming abilities in food products in Egypt, posing significant risks to food safety. Monitoring the prevalence and antimicrobial resistance profile of L. monocytogenes in dairy and meat products is crucial to enhance their safety.